Combined Transcavernous and Kawase's Approach for Gross Total Resection of a Cavernous Sinus Meningioma - Elshamy, Walid; Ozaydin, Burak; Pyle, G. Mark; Baskaya, Mustafa K. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Microsurgery of cavernous sinus (CS) lesions is generally considered to be associated with a high rate of morbidity and cranial nerve deficits. The success for surgical removal of CS meningiomas is debatable and achieving a good functional outcome with preservation of the cranial nerves is the goal. Surgery of these lesions is challenging, recurrence rates are high, and therapeutic strategies remain controversial. In this video, we present a case of a CS meningioma that extended to Meckel's cave and the posterior fossa in a 46-year-old woman with history of a left-sided cerebellopontine angle World Health Organization (WHO) grade-I meningioma with extension to the left CS. Seven years ago, she had a microsurgical resection of a Cerebellopontine angle (CPA) meningioma. She later received radiotherapy for the slowly growing meningioma of the posterior CS. The patient presented with newly onset headache and facial pain. Magnetic resonance imaging (MRI) showed a meningioma of the left CS and Meckel's cave extending into the ambient cistern, with a mild mass effect on the pons, and a size increase compared with prior imaging. Since this area previously received radiotherapy, and the patient was symptomatic from trigeminal compression, the decision was made to proceed with surgical resection of the tumor via combined transcavernous and anterior petrosectomy. Postoperatively, the patient woke up with the same neurological status. MRI confirmed gross total resection of the tumor. The histopathology was a WHO grade-II chordoid meningioma. The patient is currently receiving radiotherapy. This video demonstrates the surgical approach and the resection steps of this pathology.The link to the video can be found at: https://youtu.be/HrU1VOzUGWU.
Keywords: cavernous sinus; chordoid meningioma; Kawase's approach; Meckel's cave; transcavernous approach